2002
DOI: 10.1002/jbm.10179
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐releasing potential of vancomycin‐loaded porous hydroxyapatite blocks implanted into MRSA osteomyelitis

Abstract: Although antibiotic-loaded hydroxyapatite blocks have been used for the treatment of chronic osteomyelitis, their long-term potential for releasing antibiotic into human bones is not well known. Five patients with chronic osteomyelitis due to methicillin-resistant Staphylococcus aureus (MRSA) infection were effectively treated with local implantation of vancomycin-loaded hydroxyapatite blocks. Blocks were removed during the following reconstructive surgeries when the releasing capability of the blocks, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…Drug delivery systems for a clinical use are based on polymers, e.g. polymethylmethacrylate (PMMA) [6,7], degradable polylactic-co-glycolic acid (PLGA) [8,9], as well as on ceramic matrices like calcium phosphates (CaP) [10,11], nanoporous alumina (Al 2 O 3 ) [12,13] and silicon carbide (SiC) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery systems for a clinical use are based on polymers, e.g. polymethylmethacrylate (PMMA) [6,7], degradable polylactic-co-glycolic acid (PLGA) [8,9], as well as on ceramic matrices like calcium phosphates (CaP) [10,11], nanoporous alumina (Al 2 O 3 ) [12,13] and silicon carbide (SiC) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, vancomycin-containing hydroxyapatite blocks were implanted into 5 patients suffering from osteomyelitis induced by methicillin-resistant S. aureus. Rapid and intensive antibiotic outfl ow was observed from the carrier in the fi rst 4 weeks, and 90% of the vancomycin was released within 3 months [19] . Experiments on the elution mechanism and release kinetics of gentamycin-containing bone cement revealed that the outfl ow of the antibiotic is slower from the deeper layers [1] .…”
Section: Discussionmentioning
confidence: 99%
“…www.intechopen.com polylactides (Mader et al, 1997;Schmidmaier et al, 2006), copolymers of lactide and glycolide (Mader et al, 1997;Ambrose et al, 2003), polycaprolactone (Burd et al, 2001;Le Rey et al, 2003), hydroxyapatite and glass ceramics (Saito et al, 2002;Makinen et al, 2005;Zalewska & Ginalska, 2009), calcium sulfate (Nelson et al, 2002), and fibrin sealant implants (Mader et al, 2002) have already been investigated for use as antibiotic delivery systems. Prevention and treatment of osteomyelitis, particularly associated with orthopaedic implant surgery, have been the focus of many studies, since in most surgical procedures that include the incorporation of implants, the tissue-implant surface is especially prone to microbial contamination.…”
Section: B Amentioning
confidence: 99%